DINAMISASI TRADISI ISLAM DI ERA GLOBALISASI: Studi atas Tradisi Keagamaan Kampung Jawa Tondano - Yusno Abdullah Otta (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
There are signifiant relationship between modernization andm religion in the modernization and globalization era. In the context of Indonesia, religion, the teachings and traditions, preserved as a fundamental basis of morality to inflence the flw of modernization. Indonesian society, in general, divided into two groups of “modernist” and “traditional”. This grouping occurs because, from a historical perspective, the existence of Islam in Indonesia is experiencing a collision with various forms of local syncretic and, also, with Western civilization, especially, in the period of colonialism, the Christian religion, as happened in the village of Tondano Java, in particular, and other areas in Indonesia, in general. The result of research shows that all the tradition in this Tondano Javanese village today is still carried out consistently by the citizens. Flow of modernization and globalization were not many signifiant impacts for the implementation of these various religious traditions.